Understanding mechanisms of impact from community-led delivery of HIV self-testing: Mediation analysis of a cluster-randomised trial in Malawi - Pitchaya P. Indravudh; Fern Terris-Prestholt; Melissa Neuman; Moses K. Kumwenda; Richard Chilongosi; Cheryl C. Johnson; Karin Hatzold; Elizabeth L. Corbett; Katherine Fielding (Public Library of Science (PLoS), 2022)
Community HIV strategies are important for early diagnosis and treatment, with new self-care technologies expanding the types of services that can be led by communities. We evaluated mechanisms underlying the impact of community-led delivery of HIV self-testing (HIVST) using mediation analysis. We conducted a cluster-randomised trial allocating 30 group village heads and their catchment areas to the community-led HIVST intervention in addition to the standard of care (SOC) or the SOC alone. The intervention used participatory approaches to engage established community health groups to lead the design and implementation of HIVST campaigns. Potential mediators (individual perceptions of social cohesion, shared HIV concern, critical consciousness, community HIV stigma) and the outcome (HIV testing in the last 3 months) were measured through a post-intervention survey. Analysis used regression-based models to test (i) intervention-mediator effects, (ii) mediator-outcome effects, and (iii) direct and indirect effects. The survey included 972 and 924 participants in the community-led HIVST and SOC clusters, respectively. The community-led HIVST intervention increased uptake of recent HIV testing, with no evidence of indirect effects from changes in hypothesised mediators. However, standardised scores for community cohesion (adjusted mean difference [MD] 0.15, 95% CI -0.03 to 0.32, p = 0.10) and shared concern for HIV (adjusted MD 0.13, 95% CI -0.02 to 0.29, p = 0.09) were slightly higher in the community-led HIVST arm than the SOC arm. Social cohesion, community concern, and critical consciousness also apparently had a quadratic association with recent testing in the community-led HIVST arm, with a positive relationship indicated at lower ranges of each score. We found no evidence of intervention effects on community HIV stigma and its association with recent testing. We conclude that the intervention effect mostly operated directly through community-driven service delivery of a novel HIV technology rather than through intermediate effects on perceived community mobilisation and HIV stigma.